Takotsubo syndrome – A close connection to the brain: A prospective study investigating neuropsychiatric traits. (September 2016) - Mayer, Kristina N.; Ghadri, Jelena-Rima; Jaguszewski, Milosz; Scherff, Frank; Saguner, Ardan M.; Kazemian, Elycia; Baumann, Christian R.; Jenewein, Josef; Tsakiris, Manos; Lüscher, Thomas F.; Brugger, Peter; Templin, Christian
Abstract: Background: Takotsubo syndrome (TTS) is frequently triggered by a stressful event. Overactivation of the sympathetic nervous system has been hypothesized as the underlying mechanism. In a prospective, cross-sectional, single center study we aimed to investigate neuropsychiatric traits in patients with TTS. Methods: Twenty-six patients with TTS with a median latency of 17.5 months from their index event underwent detailed medical examination, neuropsychologic examination, and Holter-ECG and were screened for psychiatric comorbidities, chronic stress and personality traits with questionnaires. Results: 38.5% (10/26) of patients suffered from a neurological disease, and 50.0% (13/26) from at least one mental disorder. In 23.1% (6/26) the hospital anxiety scale (HADS–A) was suspicious for an anxiety disorder. There was a high prevalence of left-handedness (19.2%; 5/26). Despite good performance in cognitive testing, 11 patients had an abnormal score in the fatigue severity scale. Recovery of cardiac function was documented, although symptoms in 69.2% of patients persisted. An increase in the root mean square of the successive differences (RMSSD) (p = 0.01) was noted on the Holter-ECG. Conclusion: The study highlights a high prevalence of psychiatric and neurologic comorbidities in patients with TTS, which so far have been under-diagnosed. Future studies will have to show whether these patients might benefit from a combined psychocardiologic rehabilitation. Highlights: Persisting symptoms despite recovery of cardiac function is common. TTC patients show good neuropsychologic functioning, but there is high prevalence of fatigue. Psychiatric comorbidities seem to be under-diagnosed in patients newly diagnosed with TTC.